Comparative Effects of Microalgal Species on Growth, Feeding, and Metabolism of Pearl Oysters, Pinctada fucata martensii and Pinctada maxima - Ye, Bingcong; Gu, Zhifeng; Zhang, Xingzhi; Yang, Yi; Wang, Aimin; Liu, Chunsheng (Frontiers in Marine Science, 2022)
Pinctada fucata martensii and P. maxima are two main traditional pearl oyster species that can produce seawater pearls. Our previous study showed a higher clearance rate (CR) and growth performance in P. f. martensii than in P. maxima fed with Isochrysis galbana. In this study, the P. f. martensii and P. maxima juveniles of two sizes (large and small) were fed with six different microalgae diets [I. galbana (I), Platymonas subcordiformis (P), Chaetoceros muelleri I, I+P, I+C, and P+C] to evaluate the differences in growth, feeding, and metabolism between two pearl oyster species. After 60 d of the rearing period, P. f. martensii and P. maxima fed with mixed microalgae showed a significantly higher relative growth rate (RGR) than those fed with single microalgae (P< 0.05). The RGRs were significantly higher in P. f. martensii than those in P. maxima fed with the same diets (P< 0.05). The RGRs showed a decreasing tendency with the growth in both pearl oyster species. The CRs of pearl oysters fed with mixed microalgae were significantly higher than those fed with single microalgae (P< 0.05), and the CRs of P. f. martensii were significantly higher than those of P. maxima fed with the same diets (P< 0.05). Significantly lower respiration rates (RRs) were observed in small-size P. f. martensii groups fed with I, P, and I+P diets and all large P. f. martensii groups compared to P. maxima fed with the same diets (P< 0.05). Higher activities of amylase, cellulase, lipase, and pepsin in P. f. martensiiwere observed compared to P. maxima fed with the same diets at two sizes. The pepsin activities in P. maxima decreased with the growth, while there were no consistent pepsin activities of P. f. martensii with the growth. The carbonic anhydrase activities in P. maxima were significantly higher than those in P. f. martensii fed with the same diets (P< 0.05). The carbonic anhydrase activities were highest in the I+C diet group, followed by C+P and I+P, I, C, and P groups. Significant differences were observed among different diet groups in the same pearl oyster species (P< 0.05). Our results suggest that the lower CR and activities of digestive enzymes and higher RRs and activities of carbonic anhydrase may cause a lower growth rate of P. maxima compared to P. f. martensii.